Esensi Alam Semesta Beserta Tujuannya dalam Perspektif Filsafat Pendidikan Islam - Khairani, Aulia; Rahman, Aulia; Hasanah, Nur Arifah; Paramitra, Tiara (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Nature is a form of power created by the Almighty God. Seeking the extraordinary creation shows how beautiful the created nature is. All types of objects that show beauty are the great works of Allah SWT. The essence of the universe is Allah's intention to create the universe for humans. The purpose of God in creating the universe is basically a means to convey information to humans and evidence of the existence and omnipotence of Allah SWT that essentially there is the Almighty who rules this universe and creates this universe without any mistakes. For example, night cannot precede day, planets revolve along circular paths until the arrival of the final judgment, and so on. Basically, nature is nothing but Allah SWT. That is why the spectrum of nature is so vast. The universe was created to store so many secrets, because the formation process is very complex and its inhabitants are diverse, making it an interesting study. Nature has the same root word as address, which means something that, if we follow it, we arrive at the intended destination. This means that if we seriously study nature, it leads us to its creator, namely Allah SWT. Nature is also related to the word science, which shows that the essence of the universe is full of scientific mysteries. Let's look at the philosophy of Islamic education, the essence of this universe is not just a place to live, but the universe is actually a place of learning for humans.